Brown rice and pulses for the development of shelf-stable and low glycemic index ready-to-eat meals. (January 2023) - Baggio, Anna; Federici, Enrico; Gentilucci, Valentina; Folloni, Silvia; Dall'Asta, Margherita; Bernini, Valentina; Pellegrini, Nicoletta; Vittadini, Elena
Graphical abstract: Highlights: Ready-to-eat meals with brown rice and pulses were developed, sterilized, and stored. Both formulated meals had a low glycemic index (43.5 and 31.8). Different formulations affected the consumer acceptability. Hardness increase during the storage was not perceived by consumers. Abstract: Shelf-stable low glycemic index ready-to-eat (RTE) risotto meals (in pouches) containing brown rice and pulses (recipe A = chickpeas; recipe B = lentils, and beans) were developed, stored for 12-months at room temperature, and characterized over time. RTE meals were heated in microwave (replicating home consumption procedure), and analyzed for in vitro starch digestibility, textural attributes, and consumer acceptability. Digestible starch fractions were similar in the formulations during storage, and in vivo testing demonstrated low glycemic indexes (recipe A = 43.5 ± 6.8; recipe B = 31.8 ± 6.5) for the two meals. Hardness of risotto components increased during storage and microwave heating did not fully recover textural attibutes characteristic of the fresh product. Consumers' (50) acceptability remained high (>5.5 out of 9) until the end of storage. This study demonstrates brown rice with pulses can be used for developing stable and accepted ready-to-eat meals having low glycemic indexes.